Inverted solar cells with thermally evaporated selenium as an active layer - Liu, Wenbo (2021)
Because of its less toxicity and direct band gap, selenium (Se) has been considered as a promising single-element absorber in photovoltaics. In this work, a vacuum-evaporated selenium film has been applied in the inverted p-i-n device structure. After the gradual annealing process, the crystalline Se film could work well as an active layer on the top of a tellurium/poly(3,4-ethylenedioxythiophene) polystyrene sulfonate /ITO substrate, and phenyl-C61-butyric acid methyl ester was used as the electron transport layer to fulfill the configuration of solar cells. In our research, we found that the deposition rate had great influence on the orientation and grain size of crystalline Se in films as well as on the surface roughness of the annealed Se films. By controlling the thermal evaporation rate of Se, the grain orientation could be uniformly located along the (100) plane with larger grain sizes, which efficiently improved the open current voltage and power conversion efficiency of devices. The device based on the Se layer with the deposition rate of 0.3 nm/s possessed the highest efficiency (3.9%). Moreover, the issues that may impede the application of Se in the inverted solar cell structure and their possible solutions have been discussed.